Lipid Transporter Activity-Related Genetic Polymorphisms Are Associated With Steroid-Induced Osteonecrosis of the Femoral Head: An Updated Meta-Analysis Based on the GRADE Guidelines - Chen, Xiantao; Zhang, Leilei; Liang, Dawei; Li, Jing; Liu, Fenzhi; Ma, Hongxia (Frontiers in Physiology, 2018)
Aims: The purpose of this study was to assess the relationship between genetic variants and steroid-induced osteonecrosis of the femoral head (SONFH) in steroid use populations. Methods: We searched the public databases up to April 15, 2018. This study analyzed only the single-nucleotide polymorphisms (SNPs) that have appeared in more than three studies and assessed the level of evidence by classifying the outcomes according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Results: The ABCB1 rs1045642 C>T mutation had a protective effect against SONFH in the allelic model (I2 = 50.2%; OR: 0.74; 95% CI: 0.55–1.00; p = 0.046). The rs2032582 mutation in the ABCB1 gene showed no relationship to SONFH (allelic model: I2 = 63.4%; OR: 0.85; 95% CI: 0.58–1.23; p = 0.382). In ApoB rs693, four models showed that mutations can increase SONFH risk, but the allelic model did not. The ApoB rs1042031 mutation increased SONFH risk in the dominant model (I2 = 50.3%; OR: 2.90; 95% CI: 1.49–5.66; p = 0.002). Conclusion: An allelic model of ABCB1 rs1045642 showed that mutations have a protective effect against SONFH at a very low level of evidence. The mutations in ApoB rs693 and rs1042031 increase the SONFH risk with moderate levels of evidence.